The mTOR signaling pathway as a treatment target for intracranial neoplasms. (27th August 2014) - Pachow, Doreen; Wick, Wolfgang; Gutmann, David H.; Mawrin, Christian
Abstract: Inhibition of the mammalian target of rapamycin (mTOR) signaling pathway has become an attractive target for human cancer therapy. Hyperactivation of mTOR has been reported in both sporadic and syndromic (hereditary) brain tumors. In contrast to the large number of successful clinical trials employing mTOR inhibitors in different types of epithelial neoplasms, their use to treat intracranial neoplasms is more limited. In this review, we summarize the role of mTOR activation in brain tumor pathogenesis and growth relevant to new human brain tumor trials currently under way using mTOR inhibitors.